Halwa timun - Shabudin, Muhammad Ikhwan; Sinong, Grace Flavyeliz; Jasni, Nur Aziemah; Fitri Said, Rozlianah (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The surplus production of cucumber (Cucumis sativus) leads to significant post-harvest and income losses for farmers. A value-added product, halwa timun, is innovated to sustain the shelf-life of cucumbers, aiming to reduce food wastage and to identify the potential market of products. Halwa timun, known as a sweet confection, is produced through the process of pickling using sugar coating. The product has a soft, chewable, mild crispy texture with a classic sweet taste that is suitable for any occasion and for diverse consumers at affordable prices. The innovation of halwa timun fosters agropreneurship skills that empower local communities to adopt value-added processing techniques, creating a new revenue stream for them. The innovation aids in reducing economic loss as well as enhancing sustainable agribusiness, contributing to Malaysia's broader goals of food security and green innovation. The development of halwa timun products also aligns with SDG-3 that highlights the nutritious value of cucumber-based products and SDG-12, elevating farmer’s income and promoting sustainable agriculture.